Sistem Informasi Perbaikan Komputer Di Aditama Computer Boyolali Berbasis Android - Ahmad Jamaludin; Donna Setiawati; Fariyono Fariyono (JITU : Journal Informatic Technology And Communication, 2020)
Research titled System Information Acceptance Services Aditama Android based.Aditama Computer is one of the company engaged in the service and sale of computers in Boyolali such as laptops, PCS, printers, CCTV, scanners, Fingerspots, LCD projectors.This business was established from 2003 and address at Jalan Kenanga No.14 Boyolali, Boyolali Sub-district, Boyolali district. The administration system of service acceptance on Aditama Computer is still simple, admin fill in the Entry service input form, and Rekap service data also still recab through the book.And that often happens admins are often late in giving information until the work of the computerThis makes it a frequent customer to ask admins directly through a short message.Itupun admin is also long in responding to customers. The purpose of this research is to design, implement, and test the service acceptance information system in Aditama Computer, producing information system of service acceptance to improve services in Aditama Computer.Methodelogi Research used is a waterfall, modeling objects using UML.For coding using PHP MySQL, and Android client. The result is an information system to facilitate the service to the customers.